The original application of hybrid lens in micromeasurements for optical coherence tomography - Egorov, D. I (SPIE, 2018)
Our study focuses on popular subjects – the development of new optical measuring instruments in microscopy, coupled with optical coherence tomography (OCT). We have proposed to use hybrid hyperchromatic lenses in the schemes of spectral OCT with switchable wavelength. Change wavelength of optical radiation in the system with a hybrid lens allows accurate focusing on the surface areas of different depths, or in other words, to produce layer-by-layer scan and construction of a three-dimensional image of the investigated object with high quality. The results of our work are the development of new methods of calculation hyperchromatic hybrid lenses. The use of our optical systems in the spectral optical coherence tomography will allow to increase the speed of a spectral scan, to simplify the method of processing the measurement results, to increase the longitudinal and transverse resolution of the resulting images. In our article, we cite examples of optical schemes designed hybrid lenses, quick method of calculation of such systems, the results of aberration analysis and evaluation of the quality of the received image.